German Unification : What Have We Learned From Multi-Country Models? - Gagnon, Joseph; Masson, Paul.; McKibbin, Warwick (Washington, D.C. : International Monetary Fund, 1996)
This study reviews early simulations of the effects of German unification using three different rational-expectations multi-country models. Despite significant differences in their structures and in the implementations of the unification shock, the models delivered a number of common results that proved reasonably accurate guides to the direction and magnitude of the effects of unification on key macroeconomic variables. Unification was expected to give rise to an increase in German aggregate demand that would put upward pressure on output, inflation, and the exchange rate, and downward pressure on the current account balance. The model simulations also highlighted contractionary effects of high German interest rates on EMS countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet